2016
DOI: 10.1017/s0047279416000374
|View full text |Cite
|
Sign up to set email alerts
|

‘You can Spend Time. . .But not Necessarily be Bonding with Them’: Australian Fathers’ Constructions and Enactments of Infant Bonding

Abstract: Governments are increasingly implementing policies that encourage early father-infant bonding. However, to date, research has not systematically examined fathers’ perspectives and experiences of early bonding. Using a social constructionist embodiment perspective we argue that paternal bonding is best conceived as a process of repeated, embodied performances that are shaped by gendered parenting discourses. Drawing on 100 semi-structured interviews with a diverse group of Australian fathers of young infants, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…; Brady et al. ). It is also likely that temporal experiences associated with time pressure will continue to evolve for women (and men) as workplaces and social relations become more liquid, mobile and networked.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…; Brady et al. ). It is also likely that temporal experiences associated with time pressure will continue to evolve for women (and men) as workplaces and social relations become more liquid, mobile and networked.…”
Section: Resultsmentioning
confidence: 98%
“…; Brady et al. ) show that it is women who are predominantly taking up time flexibility measures to care for their children, particularly post‐birth. This time imbalance between male and female employees with caring responsibilities suggests policymakers need to reconsider incentives, campaigns or auditing of employed fathers’ workplace flexibility arrangements as possible ways to encourage the uptake of such measures by men (Bittman et al.…”
Section: Policy Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, although fathers' overall time with children increases when there are two or three children in the household (compared with when there is one child in the household), fathers' time with individual children decreases (Price, 2008), primarily because parents are required to distribute their time amongst more than one child. In one qualitative study drawing on interview data from the DAPP evaluation, Brady, Stevens, Coles, Zadoroznyj, and Martin (2017) 16 found that fathers who had multiple children in the household tended to spend more time with older children while mothers maintained primary responsibility for infant care. This suggests gendered patterns of caregiving; that overall parents do not only specialise in certain roles relating to paid work and caregiving, but when there are multiple children in the household, parents may specialise in certain types of care.…”
Section: Number Of Children In the Householdmentioning
confidence: 99%